2022
DOI: 10.24036/8851412612022627
|View full text |Cite
|
Sign up to set email alerts
|

Pergeseran Makna Sungai Kahayan bagi Masyarakat Dayak Ngaju di Desa Bukit Rawi Kabupaten Pulang Pisau

Abstract: Sungai memiliki beragam makna bagi setiap orang. Bagi masyarakat Dayak, sungai adalah pusat kehidupan, demikian juga dalam pandangan masyarakat Dayak Ngaju. Masyarakat menjadikan sungai sebagai pusat kegiatan ritual, sosial dan pusat ekonomi. Bahkan, masyarakat Dayak Nyaju sendiri menggunakan nama Sungai sebagai identitas mereka. Namun beberapa tahun belakangan, kehidupan masyarakat sudah mulai beralih dan pemanfaatan sungai jauh berkurang kecuali untuk kepentingan ekonomi. Hal ini menyebabkan terjadinya perge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Therefore, a theology's existence lies within the transformative process (prima facie) (M. T. Telhalia, 2017; T. Telhalia, 2016Telhalia, , 2023T. Telhalia & Natalia, 2021Wainarisi et al, 2023;Wainarisi, 2021bWainarisi, , 2021aWainarisi, , 2021dWainarisi, , 2021cWainarisi, , 2023Wainarisi & Tumbol, 2022a;Wirawan, 2021;Wirawan et al, 2023). Transformation requires critical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a theology's existence lies within the transformative process (prima facie) (M. T. Telhalia, 2017; T. Telhalia, 2016Telhalia, , 2023T. Telhalia & Natalia, 2021Wainarisi et al, 2023;Wainarisi, 2021bWainarisi, , 2021aWainarisi, , 2021dWainarisi, , 2021cWainarisi, , 2023Wainarisi & Tumbol, 2022a;Wirawan, 2021;Wirawan et al, 2023). Transformation requires critical analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The authors assumed that there were symptoms of group phenomenon, such as "understanding the method/strategy" and the term "orderly" in group activities and discussions. Whilst the authors suspected that there was a psychological symptom among students, namely self-confidence generated by the presence of peers around and supporting them, especially in one topic of discussion of group work (Andiny, 2020;Angellyna & Tumbol, 2022;Herrera, 2019;Mariani, 2020;Mariani dkk., 2023;Munte, 2018bMunte, , 2018aNugrahhu, 2021;PAHAN dkk., 2014;Pahan, 2020;SUGIYANTO dkk., 2014;Supardi, 2014;Susanto dkk., 2022;Tanyid, 2019;Telhalia, 2023;Triadi, Prihadi, dkk., 2022;Tumbol, 2020;Veronica, 2022;Veronica & Munte, 2022;Wainarisi & Tumbol, 2022a;Widyasari, 2021;Wulan, 2005;Wulan & Sanjaya, 2022). Furthermore, amidst pessimistically active knowledge sharing learning strategies in the school context in Tumbang Talaken, the 15 years old resource person breathed some fresh air that there was hope their region would increasingly develop and would be able to be implemented even beyond the critical analysis stage of the learning stimulus by their teacher.…”
Section: Resultsmentioning
confidence: 99%
“…In his opinion, the culmination of these strategies has an evaluative nature to determine the understanding level of each learner. The authors found that evaluation became important, especially in primary schools at the district level throughout Central Kalimantan (Byczynski dkk., 2022;Dela dkk., 2022;Hasan dkk., 2023;Munte, 2022b;Munte & Korsina, 2022;Setiawan dkk., 2022;Sinta dkk., 2022;Stepania & Setianti, 2022;Wainarisi, 2021aWainarisi, , 2021bWainarisi dkk., 2022bWainarisi dkk., , 2022aWainarisi & Tumbol, 2022a. Importance of the evaluation consists of evaluating not only the learners but also the progress of their own capabilities during the learning process, including the active knowledge sharing learning method.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, while the spirit touches on culture, it also touches on religion. For instance, as through Lambung's origin or identity, in Christianity, this spirit is often raised by Old and New Testament figures (Angellyna & Tumbol, 2022;Susila, 2022bSusila, , 2022aSusila, , 2022c Wainarisi, 2023;Wainarisi, 2021aWainarisi, , 2021dWainarisi, , 2021cWainarisi, , 2021bWainarisi, , 2023Wainarisi et al, , 2023Wainarisi & Tumbol, 2022aWK GINTER et al, 2009).…”
Section: Tarian Giring-giring Musikalitas Budaya Dan Dayak Kalimantan...mentioning
confidence: 99%